Centrosomal AKAP350 modulates the G1/S transition - Mattaloni, Stella Maris (2013)
AKAP350 (AKAP450/AKAP9/CG-NAP) is an A-kinase anchoring protein, which recruits multiple signaling proteins to the Golgi apparatus and the centrosomes. Several proteins recruited to the centrosomes by this scaffold participate in the regulation of the cell cycle. Previous studies indicated that AKAP350 participates in centrosome duplication. In the present study we specifically assessed the role of AKAP350 in the progression of the cell cycle. Our results showed that interference with AKAP350 expression inhibits G1/S transition, decreasing the initiation of both DNA synthesis and centrosome duplication. We identified an AKAP350 carboxyl-terminal domain (AKAP350CTD), which contained the centrosomal targeting domain of AKAP350 and induced the initiation of DNA synthesis. Nevertheless, AKAP350CTD expression did not induce centrosomal duplication. AKAP350CTD partially delocalized endogenous AKAP350 from the centrosomes, but increased the centrosomal levels of the cyclin-dependent kinase 2 (Cdk2). Accordingly, the expression of this AKAP350 domain increased the endogenous phosphorylation of nucleophosmin by Cdk2, which occurs at the G1/S transition and is a marker of the centrosomal activity of the cyclin E-Cdk2 complex. Cdk2 recruitment to the centrosomes is a necessary event for the development of the G1/S transition. Altogether, our results indicate that AKAP350 facilitates the initiation of DNA synthesis by scaffolding Cdk2 to the centrosomes, and enabling its specific activity at this organelle. Although this mechanism could also be involved in AKAP350-dependent modulation of centrosomal duplication, it is not sufficient to account for this process.